PENGARUH GAYA KEPEMIMPINAN DAN KINERJA GURU TERHADAP PENILAIAN KINERJA KEPALA MADRASAH - Mukh Khusnaini (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the effect of leadership style and teacher performance on the Madrasah Principal Performance Assessment (PKKM) across Primary Madrasahs (Madrasah Ibtidaiyah) in Limpung District. The central issue examined is the extent to which managerial leadership factors and educator productivity contribute directly to the overall effectiveness of the madrasah principal. Method: A quantitative research design with an exploratory survey approach was employed. The study population comprised all Primary Madrasah teachers in Limpung District, with sample selection conducted through proportional random sampling. Primary data were collected using structured questionnaires that underwent validity and reliability testing, and were subsequently analyzed using multiple linear regression to test the hypotheses. Results: The findings indicate that leadership style has a positive and significant effect on the principal performance assessment results. Similarly, teacher performance significantly contributes to supporting the achievement of PKKM indicators. Simultaneously, both independent variables play a crucial role in enhancing quality standards, governance, and institutional accountability. Novelty: This study underscores the novel insight that the success of a madrasah principal heavily relies on integrating transformative communication styles with consistent, high-quality teacher performance in the classroom.